2012
DOI: 10.1080/17458080.2011.597435
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO2, Ag-doped TiO2 nanoparticle and TiO2–SBA-15 nanocomposites using simple aqueous solution-based chemical method and study of their photocatalytical activity

Abstract: Nanocrystalline TiO 2 , Ag-doped TiO 2 and TiO 2 -SBA-15 nanocomposites have been synthesised using a simple aqueous solution-based chemical method. Nanocrystalline TiO 2 was synthesised by calcining the precursor prepared by using ethylenediamine tetraacetic acid and TiCl 3 in aqueous medium. Formation of crystalline phase (anatase, rutile or mixed phase) and crystallite size were found to be dependent on calcination temperature. To enhance the photocatalytic activity, Ag-doped TiO 2 was synthesised by doping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…The wall thickness calculated from the XRD pattern using the equation (Wt = 2 d (100) /3 1/2 − pore diameter) was found to be 5.70 nm, in agreement with previous reports [ 11 ]. A broad peak at 2 θ = 24° was observed, and it was attributed to the amorphous SiO 2 character [ 14 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The wall thickness calculated from the XRD pattern using the equation (Wt = 2 d (100) /3 1/2 − pore diameter) was found to be 5.70 nm, in agreement with previous reports [ 11 ]. A broad peak at 2 θ = 24° was observed, and it was attributed to the amorphous SiO 2 character [ 14 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have been applied for Ag/TiO 2 photocatalysts synthesis with different morphologies, including impregnation, sol-gel, co-precipitation, hydrothermal, photo deposition process, etc. (Naik et al 2013;Harikishore et al 2014;Sarteep et al 2016;Wenderich and Mul 2016;Zhang et al 2016b;Zheng et al 2019;Abbad et al 2020). Each synthesis method has its own advantages and shortcomings in terms of performances and preparation.…”
Section: Ag/tio 2 Photocatalystmentioning
confidence: 99%
“…The results showed that the TiO 2 -SBA-15 nanocomposites exhibited a high methyl orange removal efficiency of 81 % even at a very low TiO 2 loading of 10 wt %. [136] Guo et al also obtained a similar result when employing the TiO 2 @SBA-15 composites for photocatalytic oxidative desulfurization, reaching a high DBT removal rate of 96.1 % in a reaction time of 90 min. [94] Wang et al used the ZSM-5 material for ultra-deep desulfurization of catalytically cracked gasoline and achieved excellent desulfurization results.…”
Section: Structure Modificationsmentioning
confidence: 62%
“…synthesized TiO 2 ‐SBA‐15 nanocomposites using a simple aqueous solution‐based chemical method. The results showed that the TiO 2 ‐SBA‐15 nanocomposites exhibited a high methyl orange removal efficiency of 81 % even at a very low TiO 2 loading of 10 wt % [136] . Guo et al.…”
Section: Solutions To Podsmentioning
confidence: 97%